Quantitative Evaluation of Different Impression Induced by Inhalation of Olfactory Stimulus (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study is the pursuance of useful evaluation index which can estimate the differentimpression obtained by inhalation of several olfactory stimuli. For this purpose, the principal factorswhich could determine the impression of olfactory stimulus were attempted to identify. Then the heartrate variability and the cerebral nervous activity were monitored as physiological response. Furthermorethe relationship among the factor scores of principal factors and these physiological responses wereinvestigated. As the result, the principal factor of ‘relaxation’ could be estimated accurately with theconcentration of the oxy haemoglobin in comparison with index of heart rate variability.
Keywords: Olfactory Stimulus; Quantitative Evaluation; Autonomic Nervous Activity; Cerebral Nervous Activity